PENGARUH PEMBELAJARAN MODEL PAIR CHECK TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATAKULIAH PERENCANAAN PENGAJARAN - Sri Rahmah Dewi Saragih (Universitas Asahan, 2019)
This study aims to determine whether there is a significant influence between mathematical problem solving abilities of students who are taught using cooperative learning pair check model is higher than the mathematical problem solving abilities of students who are taught by the lecture method in Mathematics teaching planning courses. The population in this study were all V semester students of the Mathematics Education Study Program FKIP UNA, taking a sample of two semesters totaling 72 students through a purposive sampling technique. The results of the study from the experimental semester obtained an average pretest of 65.1 and posttest average of 80.8. Whereas from the semester of control the average pretest was 65.5 and the posttest average was 75.1. Analysis of posttest data using the t test at the level of α = 0.05 obtained tcount = 2.75 while t table = 1.98 turned out t_count> t_tabel so that Ho is rejected and Ha is accepted. Then it can be concluded that the mathematical problem solving abilities of students taught by using the pair check learning model are higher than the students' mathematical problem solving abilities taught by the lecture method.